Large Terrace Structure Unearthed in the Heart of the City Zone of Īśānapura: Could It Be the ‘Great Hall’ Described in the Book of Sui? - Shimoda Ichita; Chan Vitharong; Chhum Menghong (Heritage)
The archaeological complex of Sambor Prei Kuk is identified with Īśānapura, the capital of the Chenla Kingdom in the early 7th century, a political predecessor to the Angkor Empire. Previous studies have largely focused on the eastern temple zone, where numerous Hindu religious structures are concentrated, while the western moated city area—presumably the core of urban and political activity—has remained underexplored. This paper presents the results of recent archaeological excavations at a large central mound within the city zone, which is hypothesized to have functioned as a key administrative facility. The excavation revealed a large-scale and uniquely configured terraced structure, unprecedented within the site, and radiocarbon dating suggests its construction dates from the mid 6th to mid 7th century. Notably, a Chinese historical source from the same period, the Book of Sui, describes a “Great Hall” in Īśānapura where the king administered state affairs. The characteristics and spatial context of the excavated structure suggest a possible correspondence with this account. In addition, LiDAR-derived topographic data identified multiple linear and structural features extending eastward from the mound, indicating that it may have stood at the rear of a more extensive administrative compound. These findings offer new insights into the urban structure of Īśānapura and the political architecture of early Khmer civilization.